Evaluating biosecurity implementation in commercial broiler poultry production in Gujarat - Joshi, Bhoomika; Rana, Khushbu; Golaviya, Akash; Jakhesara, Subhash; Koringa, Prakash; Silva-Fletcher, Ayona; Tomley, Fiona; Paleja, Haidaruliman (Frontiers in Veterinary Science, 2026)
IntroductionPoultry farming is a critical livelihood and nutrition source in India, particularly with the rapid expansion of commercial broiler production. As operations grow, strong biosecurity practices are essential to protect flock health, reduce antibiotic use, and prevent disease outbreaks. However, limited information exists on how effectively biosecurity measures are implemented in many developing regions. This study evaluated the current status of biosecurity practices in commercial broiler farms in Gujarat, India.MethodsA structured questionnaire was administered to collect data on farmer demographics, farm characteristics, and biosecurity practices. Descriptive statistics, graphical summaries, and multivariate analyses were used to assess overall trends, identify weaknesses, and highlight key challenges in biosecurity implementation.ResultsMost surveyed farms were medium-scale operations, though notable variation existed in flock size and management. Farmers were generally educated and primarily depended on poultry farming for income. Basic practices such as vaccination, manure disposal, and bird isolation were widely recognized. However, major gaps were identified in rodent control, carcass disposal (with 97% relying solely on burial), vehicle sanitation (absent in 53.85% of farms), and awareness of antimicrobial resistance (AMR), which was low among 79.49% of respondents. Over half of the farmers had never received formal biosecurity training, and many reported challenges related to limited skilled labor, financial constraints, and inadequate veterinary support.DiscussionThe findings demonstrate widespread reliance on poultry farming but highlight inconsistent adoption of critical biosecurity measures. Poor awareness of AMR, limited training, and infrastructural deficits pose substantial risks for disease spread and antibiotic dependence. Targeted interventions—including capacity-building programs, improved veterinary access, and affordable biosecurity tools—are necessary to strengthen farm resilience and support public health goals through reduced antimicrobial reliance and enhanced disease prevention.